Imobilização de lacase em nanocompósitos magnéticos com potencial aplicação para remoção de corantes em efluente têxtil. - Braz, Ana Kátia de Sousa (2023)
The use of enzymes in biodegradation of environmental contaminants has aroused great interest, with the increase in recalcitrant organic pollutants in water. Among the pollutants present in water are synthetic dyes, one of the most common pollutants and frequently found in the effluent of the textile industry. Their final destination is extremely important from an environmental point of view, because even at very low concentrations, dyes can be highly toxic to aquatic systems. Laccase enzymes have achieved prominence for degrading these types of pollutants. Lacase catalyzes the oxidation of polyphenols, aromatic compounds; moreover, they have many applications, which makes this enzyme attractive for environmental applications. However, free laccases have disadvantages such as high production cost, loss of stability, and it is not possible to recover and reuse them to make the process economically viable. Such problems can be overcome when proper immobilization techniques are employed. Thus, the immobilization of laccase in magnetic nanocomposites coated with chitosan was studied. In the first approach of this work, the objective was to study the biochemical and physical-chemical properties of laccase from the fungus Aspergillus sp., in order to provide important initial information for basic studies and for the application of laccase. In the second approach of this work, with the objective of maximizing the recovery of enzymatic activity, the best conditions for enzyme immobilization were studied. Thus, laccases immobilized on magnetic nanocomposites coated with chitosan were prepared following different combinations of enzymatic charge, pH, ionic strength and time; and later characterized by the techniques of DRX, FTIR, TGA, FRX, MEV and VSM. Finally, the enzyme and the biocatalysts produced under the best conditions of the experimental design were used in the degradation of C.I. Reactive Blue 19 and C.I. Reactive Blue 250 dyes, respectively. Biocatalysts promoted greater removal of contaminants, with 96.24 ± 0.56 of C.I. Reactive Blue 250; compared to the free enzyme, which removed 72.76 ± 1.12% of C.I. Reactive Blue 19 under the conditions tested.